2013
DOI: 10.1097/jes.0b013e318292f408
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Work Capacity in Individuals with Down Syndrome

Abstract: Low work capacity and V˙O2peak commonly are described phenomena in Down syndrome. This is accompanied by chronotropic incompetence and a high incidence of obesity. Although many causes of low work capacity in Down syndrome have been proposed, little scientific support exists. Our working hypothesis is that autonomic dysfunction is the major contributor to the low levels of work capacity in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
1
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(90 citation statements)
references
References 43 publications
6
80
1
3
Order By: Relevance
“…This could be related to both depressed sympathetic tone and response as incomplete vagal withdrawal [3,19]. Fernhall et al [19] have demonstrated that chronotropic incompetence in persons with DS limits exercise performance, consistent with findings in other clinical observations where chronotropic incompetence is a significant contributor to exercise intolerance [20]. Alterations in the sympathetic and parasympathetic modulation of heart rate are indicative of dysautonomia [21,22].…”
Section: Contents Lists Available At Sciencedirectsupporting
confidence: 61%
See 2 more Smart Citations
“…This could be related to both depressed sympathetic tone and response as incomplete vagal withdrawal [3,19]. Fernhall et al [19] have demonstrated that chronotropic incompetence in persons with DS limits exercise performance, consistent with findings in other clinical observations where chronotropic incompetence is a significant contributor to exercise intolerance [20]. Alterations in the sympathetic and parasympathetic modulation of heart rate are indicative of dysautonomia [21,22].…”
Section: Contents Lists Available At Sciencedirectsupporting
confidence: 61%
“…The pathophysiological links between chronotropic incompetence and DS remain unclear but some impaired exercise-induced adrenomedullary and sympathetic responses have been proposed [3,9,18]. This could be related to both depressed sympathetic tone and response as incomplete vagal withdrawal [3,19]. Fernhall et al [19] have demonstrated that chronotropic incompetence in persons with DS limits exercise performance, consistent with findings in other clinical observations where chronotropic incompetence is a significant contributor to exercise intolerance [20].…”
Section: Contents Lists Available At Sciencedirectsupporting
confidence: 59%
See 1 more Smart Citation
“…In addition to high rates of overweight and obesity among individuals with DS, this population commonly exhibits very low peak aerobic capacities coupled with lower than expected peak heart rates (HR peak ) (Balic, Mateos, Blasco, & Fernhall, 2000;Fernhall et al, 2009;Fernhall, Mendonca, & Baynard, 2013). While lack of motivation and understanding do not explain low work capacities achieved among individuals with DS when appropriate testing and familiarization protocols are followed (Fernhall et al, 2013), physical activity levels do not further explain this phenomenon either with activity being similar to the general population (Mendonca, Pereira, & Fernhall, 2010).…”
mentioning
confidence: 99%
“…In addition, DS patients exhibit reduced work capacity, which is attributable to an attenuated heart rate (Hr) response to exercise as well as to sympathoexcitatory challenges [11,12]. Studies suggest that such attenuated Hr and blood pressure (BP) responses in individuals with DS may be coupled with a lesser reduction in baroreflex sensitivity, which is related to a blunted sympathetic activation and to a parasympathetic withdrawal [13,14]. On the other hand, individuals with DS have an elevated arterial stiffness [15] and risk of stroke [16] so that BP control through exercise interventions could be an interesting strategy to apply in this population.…”
Section: Introductionmentioning
confidence: 99%